2011
DOI: 10.1242/dev.064444
|View full text |Cite
|
Sign up to set email alerts
|

HP1γ links histone methylation marks to meiotic synapsis in mice

Abstract: SUMMARYDuring meiosis, specific histone modifications at pericentric heterochromatin (PCH), especially histone H3 tri-and dimethylation at lysine 9 (H3K9me3 and H3K9me2, respectively), are required for proper chromosome interactions. However, the molecular mechanism by which H3K9 methylation mediates the synapsis is not yet understood. We have generated a Cbx3-deficient mouse line and performed comparative analysis on Suv39h1/h2-, G9a-and Cbx3-deficient spermatocytes. This study revealed that H3K9me2 at PCH de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 42 publications
2
86
1
1
Order By: Relevance
“…We observed HP1␥-NPM1 co-localization in the perinucleolar region, and interestingly, NPM1 was required for the efficient tethering of HP1␥ to the nucleolus. It should be pointed out that loss of HP1␥ function may negatively affect centromere clustering and cohesion processes (62)(63)(64). In fact, the loss of HP1␥ in Drosophila resulted in nucleolar deformation and fragmentation.…”
Section: Nucleoli In Npm2mentioning
confidence: 99%
“…We observed HP1␥-NPM1 co-localization in the perinucleolar region, and interestingly, NPM1 was required for the efficient tethering of HP1␥ to the nucleolus. It should be pointed out that loss of HP1␥ function may negatively affect centromere clustering and cohesion processes (62)(63)(64). In fact, the loss of HP1␥ in Drosophila resulted in nucleolar deformation and fragmentation.…”
Section: Nucleoli In Npm2mentioning
confidence: 99%
“…H3K9me2 is mainly associated with facultative heterochromatin, whereas H3K9me3 is observed at constitutive heterochromatin, particularly at pericentromeric heterochromatin (PH). In meiotic spermatogonia, both H3K9me2 and H3K9me3 reportedly are crucial for pairing of homologous chromosomes (Peters et al, 2001;Takada et al, 2011); and although H3K9, H3K27 and H4K20 modifications during the mitotic phase have been characterized histologically (Payne and Braun, 2006), their biological significance with respect to spermatogonial differentiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The cbx-3 (gene encoding HP-1γ) mutant mouse was generated by gene-trapping technology as described previously (10, 28). We found that cbx-3 − /− mice died perinatally.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, HP-1γ has been found associated with both heterochromatin and euchromatin suggesting that it participates in transcriptional repression and activation, respectively (4, 8, 9). HP-1γ interacts with the methyl groups of H3K9 through the chromodomain (CD) and with the methyl transferase SUV39-H1 and other proteins through the chromoshadow domain (CSD) (2, 3, 10). Despite these crucial in vitro observations, it is not understood if and how HP-1γ contributes to the regulation of immunity in mammals in vivo .…”
Section: Introductionmentioning
confidence: 99%